TEOLOGI KERUKUNAN BERAGAMA DALAM ISLAM (Studi Kasus Kerukunan Beragama di Indonesia) - Ghazali, Adeng Muchtar (Universitas Islam Negeri Raden Intan Lampung, 2013)
Religious affiliation and cultural diversity has become potential sources of social conflicts in Indonesia. As almost every existing religion has a truth claim, all of it’s believers fell obliged to proclaim religious teachings and values in social and national life. Viewed in this context , the biggest problem in Indonesia today is “ how theology of existing religions define themselves among other religions . This article is aimed at exploring the concept of “Tasamuh / the principle of tolerance” as one of the theological basis of the religious consciousness in Islam. The concept of tolerance in Islam is so simple and rational. Islam requires its followers to establish strict limits in the context of faith, while maintaining respect for other’s rights, individually, socially and religiously. Such an obligation is made to keep its followers not to get stuck on syncretism.